Elucidating the Role of Women From Nature : Nurture to Entrepreneurship - Mishra, Pratika; K. S., Aurobindo (AMC Indian Journal of Entrepreneurship, 2021)
In a larger context, the French word Entrepreneurship means to start a new project or to try a new opportunity. As entrepreneurship evolved in the past centuries, it brought with it innovation in production of goods and services to serve the society world-wide, but the existing literature establishes that traditionally entrepreneurship has been a male-dominated activity. Recent technological advancements coupled with the economic boom of the 1990s witnessed a spurt of women entrepreneurs making rapid strides in this hitherto male-dominated domain. This paper elucidates what makes a woman entrepreneur. Is she a born entrepreneur or trained to become so? This study aimed to explore the nature of inherent traits and the acquired or supporting eternal variables that have led to the success of the sampled women entrepreneurs. To explore further, the following important variables from the literature review were combined into categories that reflect various traits of women entrepreneurs : risk taking ability, initiative taking ability, self-motivation, leadership ability, and entrepreneurial attitude. On studying 401 women entrepreneurs, logistic regression analysis was applied to predict the success of women entrepreneurship to comprehend the prediction of ‘nature’ (internal) variables, and ‘nurture’ (external) variables covered in the research study. There exists further scope for expanding this research across multiple geographies as this data offers fruitful preliminary insights based on a single-country exploration and that too from a sample drawn only from four metros in India.